Simultaneous Sodium Hydroxide Production by Membrane Electrolysis and Carbon Dioxide Capture. Issue 12 (19th October 2017) - Yun, Haesung; Kim, Young Eun; Lee, Wonhee; Youn, Min Hye; Jeong, Soon Kwan; Park, Ki Tae; Lee, Ki Bong
Abstract: The simultaneous process of NaOH production via electrolysis of NaCl and CO2 capture was investigated due to the expectation of reduction in capital cost. It was found that seawater concentration of NaCl solution was adaptable to be used as both anolyte and catholyte and that 90 °C was the most proper temperature for NaOH production among the test conditions in this work. Under these electrolyte and temperature conditions, the simultaneous NaOH production and CO2 capture processes were conducted and more than 98.83 % of OH − was reacted with CO2 to yield aqueous carbonate solutions. Additional electrochemical CO2 capture tests were carried out depending on the different CO2 concentration of mixed gases. Abstract : A one‐step process for generation of NaOH via electrolysis of NaCl and CO2 absorption simultaneously in an electrochemical device allows reducing the capital cost in the entire process for carbonate mineral production. The simultaneous process was performed in an electrolyzer and produced aqueous carbonate/bicarbonate solutions prior to the mineralization process.